Photography in German 1919-1939. (Tokyo : Galerie Watari, 1982)
Arndt, Gertrude ; Coppola, Horatio ; Ehrhardt, Alfred ; Feininger, T. Lux ; Hajek-Halke, Heinz ; Hoepffner, Marta ; Kesting, Edmund ; Mantz, Werner ; Moholy-Nagy L. ; Munkacsi, Martine ; Renger-Patzsch, Albert ; etc.
Photography in German 1919-1939, Galerie Watari, Tokyo, July 30 - August 28 1982
English-Japanese
kunstcatalogus
Keywords: Duitsland